The Role of Religious Ethics in Regulating the use of Artificial Intelligence on Education - Nauntika, Nila Pingkan; Dartim, Dartim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyse how religious ethics, specifically Islamic ethics regulate the use of Artificial Intelligence (AI) in education. As educational institutions increasingly adopt AI for personalised learning, automated assessment, and adaptive learning systems, they face complex ethical challenges. These challenges include algorithmic bias, information hallucination, violations of academic integrity, and cognitive dependence on technology. We conducted a Systematic Literature Review (SLR) following the PRISMA protocol. Specifically, we examined English-language, Scopus-indexed articles published between 2025 and 2026, focusing on the intersection of AI, education, and ethical implications. From the initial 174 articles, we then analysed 10 of the most relevant publications in depth. The findings show that a technocratic perspective largely dominates AI applications in education, emphasising system efficiency and accuracy. However, educators and policymakers have yet to substantively integrate normative ethical dimensions and religious values. Addressing this gap, the study demonstrates that the core principles of Islamic ethics such as amanah (responsibility), 'adl (justice), maslahah (public good), and ḥifẓ al-‘aql (preservation of intellect) provide a highly relevant framework for governing AI in education equitably and human-centrically. This research integrates Islamic religious ethics as a complementary normative framework alongside modern AI ethics. This approach ensures that AI in education operates not only with technical effectiveness but also in alignment with the moral, spiritual, and higher purposes of education.